Fibroblast activation protein inhibitor (FAPI) PET for diagnostics and advanced targeted radiotherapy in head and neck cancers - Syed, Mustafa; Flechsig, Paul; Liermann, Jakob; Windisch, P.; Staudinger, Fabian; Akbaba, Sati; Körber, Stefan A.; Freudlsperger, Christian; Plinkert, Peter K.; Debus, Jürgen; Giesel, Frederik L.; Haberkorn, Uwe; et al. (European journal of nuclear medicine and molecular imaging, 2020)
Cancer-associated fibroblasts (CAFs) expressing fibroblast activation protein (FAP) have been associated with the aggressive nature of head and neck cancers (HNCs). These tumours grow diffusely, leading to extremely challenging differentiation between tumour and healthy tissue. This analysis aims to introduce a novel approach of tumour detection, contouring and targeted radiotherapy of HNCs using visualisation of CAFs: PET-CT with 68Ga-radiolabeled inhibitors of FAP (FAPI).